Perancangan Media Promosi Geomorfologi Karst Rammang-rammang Berbasis alam Sebagai Identitas Kabupaten Maros Sulawesi Selatan - Poetri, Indah Andini; Bahruddin, Muh; Riqqoh, Abdullah Khoir (Jurnal Art Nouveau, 2016)
The purpose of the design media promotion Karst Rammang-rammang is to make Rammang-rammang as the leading tourist visit in South Sulawesi that has the charm of the natural beauty that is not owned by the other regions. Research done by qualitative methods apply by doing interviews, documentation, observation and study of the library to get the data that  used in the creation of design concepts as supporters of media promotion. The concept of the research is "imemorable", this concept of the SWOT analysis, STP, and USP, so John Matheson keyword "Memorable" in the design. United Kingdom Oxford Dictionary in the dictionary "impressive" has a meaning in effect something memorable, exciting and amazing. In such event, a memorable concept has a close relationship with the beauty panorama of karst Maros Rammang-rammang. Then this will be visualized in the design creatively with visit has the attraction so give something memorable for tourists occurred at the panorama of karst, the perceived atmosphere and its potential apply Stone garden, Berua village, Pute River and that can be a tourist could provide educational value about the function role of the karst so indirectly can preserve the karst in the Rammang-rammang Maros. The result of the design of media promotion is to make the Rammang karst-rammang as the leading tourist destination in Maros South Sulawesi. Keywords:Media promotion, Karst, Rammang-rammang, Maros South Sulawesi